Thermocapillary actuation of droplet in a planar microchannel - Jiao, Zhenjun (2014)
A study on thermocapillary actuation of liquid droplet in a planar microchannel has been carried out by both theoretical modeling and experimental characterization. The driving temperature gradients are provided by four heaters at the channel boundaries. In the modeling, the temperature distributions corresponding to transient actuation are calculated, and are coupled to the droplet through the surface tensions which drive the droplet to move inside the channel. The droplet trajectories and final positions are predicted, and are compared with the experimental observations, in which a silicon oil droplet was actuated inside a 10 mm × 10 mm planar channel with four heater fabricated on the substrate plate. The results show that the droplet can be positioned anywhere in the channel, determined by a heating code related to the heating strengths. Qualitative agreement between the modeling results and experimental data, in terms of temperature distributions, droplet trajectories and positions, has been obtained.